In Vitro Study on Fallopian Tube Patency in Buffaloes - ANSARI, G M; GUPTA, H P; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
Morbid genitalia (309), obtained from freshly slaughtered she buffaloes, were examined for grossabnormalities and assessment, delineation of site and nature of blockade in the fallopian tube byuterotubal insuftlation test, salpingography and tubal histopathology. It was observed that 64.06%genitalia had different abnormalities. Further 11.32%, 39.15% and 49.51 % genitalia had bilateralblockage, unilateral blockage and bilaterally patent oviducts, respectively.
Keywords: Tubal patency; uterotubal insuftlation test; salpingography; buffalo